URBAN TOURISM IN MALAYSIA AND THE CONTEXT OF DEVELOPING COUNTRIES - ISMAIL, HAIRUL NIZAM (ASEAN Journal on Hospitality and Tourism, 2008)
This paper highlights aspects of urban tourism in developing countries and the nature of its existence. The discussion gives a focus to the context ofurban tourism in Southeast Asia, specifically, perspectives on tourism development in the cities of Malaysia. Tourism development in the cities of Malaysia can be viewed in two stages, which are after independence (after 1957) and after tourism came of age (post 1990). Both of the stages influenced on how tourism has been perceived in Malaysian cities. The discussion concludes with the implications oftourism in Malaysia cities within the context of Southeast Asia as a means to provide insights into urban tourism in developing countries. Therefore, the question of how the concept of urban tourism applies to the cities of developing countries can be considered.